Degradation of Herpes Simplex Virus-1 Viral miRNA H11 by Vaccinia Virus Protein VP55 Attenuates Viral Replication - Zou, Weixuan; Zhou, Xusha; Wang, Lei; Zhou, Grace Guoying; Chen, Xiaoqing (Frontiers in Microbiology, 2020)
Among 29 distinct miRNAs expressed by the herpes simplex virus-1 (HSV-1) during lytic infection, miR-H11, together with miR-H1 to miR-H8 are reported to locate in the RNA-induced silencing complex. miR-H11 is encoded within viral origins of replication and lies entirely within the origins of replication. However, the roles of this miRNA derived from lytic infection with HSV-1 remain unclear. Using the advantage of vaccinia virus protein VP55 (VP55)-mediated degradation of miRNAs, we constructed a recombinant virus expressing VP55 (R5502) to demonstrate that: 1) accumulation of miR-H11 from R5502 was reduced by 540-fold versus that in cells infected with wild-type HSV-1, but miR-H1 to miR-H8 which also located in the RNA-induced silencing complex were not reduced significantly from R5502 compare with wild-type HSV-1; 2) downregulation of miR-H11 from R5502 infected cells results in markedly lower viral DNA synthesis compared with wild-type HSV-1; 3) downregulation of miR-H11 also restricted viral spreading, and resulted in low accumulation of representative viral proteins and viral yields, The findings were confirmed through either using of a miR-H11 inhibitor or pre-transfection of a plasmid expressing VP55. These data suggest that miR-H11 plays a currently unidentified role in maintaining sufficient viral DNA synthesis during the course of viral infection.